Prevalence of gregarine parasites in Anadara cornea (Reeve, 1844) and its potential infectivity to Scylla sp. and Macrobrachium rosenbergii (De Man, 1879) - Haji Zakariah, Mohd Ihwan (2020)
The prevalence of gregarine parasites in wild bivalves is an important indicator for the sustainability of ecosystem health due to interdependence to survive. The data or information of the health status of wild bivalves is important for commercial crustacean culture in the future. All prominent species in the Setiu Lagoon of Terengganu state, are economically important due to the use for both local consumption and commercial in the region. This study will be an important report that can be explored regarding this parasite for the future research, tackling problems and future perspectives. The study of this parasite in the wild population has not been previously reported This undertaken study is important to ensure that the infection of this parasite will not cause a problem for the commercial bivalve’s aquaculture in Malaysia. This data obtained can be used to develop a better treatment and quarantine procedure for aquaculture. Ecosystem health status is very important to secure the future of the crustacean culture industry. This study was done to prove the existence of parasites species that commonly infect the bivalves and crustacean species in Malaysia. The detailed correlation between the prevalence of the parasites and environmental factors such as season and water quality that contribute to the intensity of the parasites are of important concern. It is important to know this information to elaborate on the complete lifecycle of this gregarine. Moreover, diagnosis of this parasite is also important to safeguard our aquaculture industry for our national future food security. The furbished information of the occurrence of the gregarine parasite will be a platform for future study in many perspectives such as development of vaccines and treatment to cure the infection. Moreover, the gregarine parasites species identification in the natural host environment is the main undertaking to be clarified. Furthermore, the study of proper prophylaxis and treatment has yet to not reported for this parasite. Importantly, results of the current study recorded that wild marine bivalves Anadara cornea (Reeve1844) is a new host for gregarine species-genus Ascogregarina. However, further study needs to be explored to detail out the specific information for this species as to elucidate a comprehensive overview of described species of the genus Ascogregarina from wild bivalves, Anadara cornea (Reeve 1844), including taxonomy, lifecycle, pathogenicity and host specificity features. The study of outbreak of this parasites infection during the rainy season should include the sedimentation analysis for better correlation of significant factor of infection. The selection of intermediate host candidates should be varied i.e., shrimp, prawn, tubeworm etc. to confirm the specific host for this parasite. Samples were collected monthly throughout 2018 in the seagrass bed area at Setiu lagoon, Terengganu, Malaysia. Forty samples were collected each month to determine the occurrence and prevalence of the parasites. The correlation between the prevalence, water quality and the seasonal factor were critically observed. The general objective of this study are to record the occurrence of gregarine parasites in wild marine bivalves Anadara cornea (Reeve, 1844) from Setiu lagoon, Terengganu, Malaysia. From the study, the total number of parasites count was n = 33,239 phagocytes from n = 480 of host samples. The total yearly prevalence of the parasites was 97.5% with a 95% confidence interval value which was CI=96.1% to 98.9%. The prevalence of the parasites was significantly high during the rainy season compared to other season (Dry and Moderate). The findings also proved that the intensity of the parasites decreased at every transition of season. The higher the level of ammonia, the lower number of parasites found. The morphological characteristic of the species was also described and the species was been confirmed by DNA analysis and found to be closely related to Ascogregarina sp. The histopathological study proved that the infections of this parasite did not induced any serious effect in the host body. The in-vitro infectivity test between intermediate host, A. cornea (Reeve, 1844) and definitive host, Scylla sp. showed a negative result as no transmission occurred between both target species. It was assumed that Scylla sp. was not a definitive host for this bivalve gregarine. This study is the first report of gregarine infection in wild marine bivalves, A. cornea (Reeve, 1844) from Setiu Lagoon, Terengganu, Malaysia. This study provided novel information on the prevalence of gregarine parasites and seasonal infection in host species in the Setiu Lagoon, and will help to optimize sustainable management strategies for use in their native environment and wildlife conservation.